Examining potential risk factors, pathways and processes associated with childhood Injury in the Longitudinal Study of Australian Children - Blakemore, T (My University, 2007)
Injury, including poisoning, is the most common cause of child death in Australia; the task of identifying risk factors for injury is therefore an important prerequisite to forming effective preventative policy and practice parameters. This paper considers the potential of a wide range of child, family and contextual characteristics to act as risk factors for injuries sustained by children in the 'child' cohort of the Longitudinal Study of Australian Children (LSAC), and it explores the interrelationships that may exist between significant risk factors. The findings support a conceptualisation of childhood injury as the result of exchanges and interactions between child, family and the broader contextual environment. These findings may also warrant examination of the most effective mix of programs and interventions to prevent childhood injury.
Keywords: Health; Health -- Injury; Health and wellbeing; Health; Injury; Health and wellbeing